2021
DOI: 10.3390/cancers13040709
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in the Interplay between Tumor Cells and Cancer-Associated Fibroblasts: Signals to Catch and Targets to Hit

Abstract: Cancer development and progression are not solely cell-autonomous and genetically driven processes. Dynamic interaction of cancer cells with the surrounding microenvironment, intended as the chemical/physical conditions as well as the mixture of non-neoplastic cells of the tumor niche, drive epigenetic changes that are pivotal for the acquisition of malignant traits. Cancer-associated fibroblasts (CAF), namely fibroblasts that, corrupted by cancer cells, acquire a myofibroblast-like reactive phenotype, are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 117 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…The cancer-associated fibroblasts-derived exosomes were shown to carry lncRNA H19, which is highly expressed in tumor stroma in comparison to tumor tissue. This lncRNA promotes stemness and chemoresistance of cancer cells and increases the frequency of tumor-initiating cells [77].…”
Section: Intracellular and Extracellular Compartmentalization Of Lncrnasmentioning
confidence: 99%
See 3 more Smart Citations
“…The cancer-associated fibroblasts-derived exosomes were shown to carry lncRNA H19, which is highly expressed in tumor stroma in comparison to tumor tissue. This lncRNA promotes stemness and chemoresistance of cancer cells and increases the frequency of tumor-initiating cells [77].…”
Section: Intracellular and Extracellular Compartmentalization Of Lncrnasmentioning
confidence: 99%
“…A recent literature survey of Salamini-Montemurri et al, has identified 215 lncRNAs being involved in OCs, of which for 157 there is experimental proof [8]. Apart from initiation, lncRNAs have been associated with many biological processes associated with metastasis [80], such as the immune response [73], radiation response [81], epithelial to mesenchymal transition (EMT) and stemness [82], cell-to-cell communication, and regulation of the microenvironment in which cells reside [77].…”
Section: The Role Of Lncrnas In Various Biological Processes Related To Ovarian Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, CAFs carry out their role of maintaining tumor characteristics by means of secreting soluble paracrine signals and releasing extracellular vesicles (EVs) [ 8 ]. Meanwhile, the aforementioned EVs, as a group of membrane-enclosed vesicles, serve as the crucial medium of intercellular communication in TME and participate in a plethora of processes associated with tumor progression, including proliferation, angiogenesis, and metastasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%